Neodymium Isotopes in Glauconite for Palaeoceanographic Reconstructions at Continental Margins: A Preliminary Investigation From Demerara Rise - Giresse, Pierre; Bayon, Germain; Tallobre, Cedric; Loncke, Lies (Frontiers in Earth Science, 2021)
Contourite sediment accumulations at continental margins are related to strong bottom water circulation, where intense winnowing can result in neoformation of authigenic grains of glauconite at the seafloor. In this study, we investigated whether such glauconite grains could faithfully record ambient bottom-water neodymium (Nd) isotopic compositions, and hence be used as paleoceanographic archives. To this purpose, we measured Nd isotopic compositions (Nd) in a series of glauconitic grains, foraminiferal assemblages, leached Fe-Mn oxyhydroxide phases and detrital clays separated from a contourite sediment record at the Demerara slope off French Guiana (IG-KSF-11; 2370 m water depth), at a location where the present-day Nd distribution along the water column is well characterized. We show that the Nd composition of core-top glauconite grains (-12.0 ± 0.5) agrees with the expected NADW-like seawater signature at the same location and water depth (-11.6 ± 0.3), while departing from measured Nd values for corresponding detrital clays (-11.3 ± 0.2), foraminiferal (-10.9 ± 0.2) and Fe-Mn oxyhydroxide fractions (-9.2 ± 0.2). This finding indicates that glauconitic grains at this particular location are probably best suited for paleoceanographic reconstructions than foraminifera and leached Fe-oxyhydroxide fractions, which appear to be influenced by sediment redistribution and the presence of terrestrial continental Fe-oxides, respectively. Using rare earth elements (REE), we tentatively propose that the acquisition of seawater Nd isotopic signatures by glauconite is controlled by the presence of authigenic REE-bearing phosphate-rich phases intertwined within clay mineral sheets, while confirming previous findings that the process of glauconitisation results in the progressive loss of REE within glauconitic grains. Preliminary paleoceanographic implications suggest strengthened bottom-water circulation of the glacial analogue of NADW at this particular location and water depth, with a Nd signature (between -10.8 to -11.5) similar to that of modern NADW.